Valorização de monoterpenos de origem natural através de processos catalíticos tandem envolvendo a reação de hidroformilação catalisada por complexos de ródio - Camila Grossi Vieira (2013)
Rhodium-catalyzed tandem hydroformylation-acetalization of a series of r-menthenic terpenes, i.e., g-terpinene, terpinolene and limonene, has been studied in ethanol solutions in the presence of PPh3 or P(O-o-tBuPh)3 as auxiliary ligands. Limonene gives the corresponding acetals in high yields in both systems. The substrates terpinolene and g-terpinene have shown an extremely low reactivity in the Rh/PPh3 system. The use of P(O-o-tBuPh)3 not only remarkably accelerated the hydroformylation of all substrates but also increased significantly the acetalization activity of the catalytic system. With the Rh/P(O-o-tBuPh)3 system, the mixtures of fragrance acetals have been obtained from these substrates in excellent combined yields. The process wasperformed under mild conditions and in the absence of acid co-catalysts. The hydroformylation of all substrates in ethanol solutions was found to be much faster than in toluene. The rhodium catalyzed hydroformylation of R-(+)-limonene in the presence of PPh3 or P(O-o-tBuPh)3 as auxiliary ligands and pyridinium r-toluenesulphonate as an acid cocatalystgave two diasteroisomers of 4,8-dimethyl-bicyclo[3.3.1]non-7-en-2-ol, useful as perfumes, in up to 96% combined yield. These alcohols were formed through the hydroformylation of limonene followed by the intramolecular ene reaction resulting in the formation of the additional carbon-carbon bond and cyclization of the primarily formed aldehyde. The cyclization step is highly stereoselective as only one diasteroisomer of the alcohol is formed from each of two diasteroisomers of aldehyde.The use of the P(O-o-tBuPh)3 ligand not only remarkably accelerated thehydroformylation compared to the system with PPh3 , but also increased significantly the cyclization step and the activity of the catalytic system.Rhodium-catalyzed hydroformylation of acyclic monoterpenic compounds, i.e., linalool and b-citronellene, has been studied in toluene and ethanol solutions in the presence of PPh3 or P(O-o-tBuPh)3 ligands. Although both substrates have a monosubstituted terminal double bond, they showed different behavior under the hydroformylation conditions. In toluene, linalool gave almost quantitatively a cyclic hemiacetal. Inethanol, the reactions occurred approximately two times faster than in toluene giving corresponding acetals derivated from linalool even in the absence of additional acid cocatalysts. In the absence of P ligands, linalool (differently from b-citronellene) was very resistant to hydroformylation in both solvents, probably, because of the chelation effect. The hydroformylation of b-citronellene in toluene solutions resulted in two isomeric aldehydes also in a nearly quantitative combined yield. In ethanol solutions, this substrate gave a mixture of aldehydes and corresponding acetals. The P(O-o-tBuPh)3 ligand exerted a remarkable effect on the reactivity of both substrates accelerating thereactions by five to twenty times as compared to the system with PPh3.In the present work, we have developed a number of efficient catalytic processes to synthesize fragrance compounds starting from the substrates easily available from natural bio-renewable resources. The methods consist from simple one-pot procedures and allow obtaining the desired products in high to excellent yields. All the compoundsobtained have a pleasant scent and can be useful as components of synthetic fragrances. In most of the reactions studied, the nature of the auxiliary phosphorous ligand and the nature of the solvent affected significantly the catalytic performance of the rhodium complex.